The Role of Leadership and its Relationship with the Performance of Community Health Volunteer: A Survey in Rural Indonesia - Rohmani, Ngatoiatu; Utari, Dewi (Disease Prevention and Public Health Journal, 2021)
Background: Community Health Volunteers (CHVs) are the manifestation of community participation to solve health issues of the community, which is reflected through Integrated Services Post or known as Posyandu activities. Therefore, CHVs selection criteria need to be upgraded to support their performance in delivering community health services. This research aimed at identifying the relationship between the role of leadership and their performance in Posyandu activities. Method: This was a cross-sectional study conducted in Purwomartani village, Sleman, with a total of 68 respondents. Data were collected using validated questionnaires to evaluate the leadership and performance of healthy volunteers. The data were analyzed using Spearman's rank correlation. Results: The respondents comprised 100% females, 71.3% were aged above 41, and 82.4% were housewives, and 83.3% completed their education up to senior high school. The study revealed that 57.4% of respondents showed excellent performance before, during, and after the Posyandu activities. Bivariate analysis revealed that the role of leadership has a significant relationship with the performance of health volunteers (p<0.05). Conclusion: Training on leadership and effective communication is needed to support the role of CHVs to motivate the community to use the facilities for better health status.